Design and Construction of a Website-Based Workplace Noise Intensity Measurement - Dewi Kurniasih; Abhi Listyo Kusuma Aji (International Journal of Marine Engineering Innovation and Research, 2025)
This study was conducted at the Surabaya State Polytechnic of Shipping (PPNS), where the Occupational Safety and Health Management System (SMK3) is implemented to ensure a safe and efficient work environment in accordance with industry standards. Currently, noise measurements are carried out manually and data recording is often not well documented. The main objective was to design a noise detection system for the construction workshop, focusing on monitoring environmental noise as part of SMK3's Hazard Identification and Risk Assessment (IBPR) process. The research method involved calculating decibel (dBA) values using regression, transmitting measurement data from the device to the server via a Wemos D1 Mini, and comparing the results with conventional sound level meter readings to identify machine noise sources. The outcome is a web-based noise detection system that automatically records measurements, shows results, and displays warnings if noise levels exceed the Threshold Limit Value (NAB).